Revolution in the perspective of khilafah - Zainuddin Losi; Asriani Asriani; Andi Nur Fiqhi Utami; Nizar Nizar (Indonesia Prime, 2021)
The collapse of the Khilafah in 1924 caused Hizb ut-Tahrir (HT) to fight for the re-establishment of the Khilafah. The expected change in the struggle is a fundamental change to people's thinking, outlook on life and system of government so that the change is more appropriately referred to as revolution. This paper examines HT's perspective on the method of revolution based onthe stages of the Prophet's da'wah. Thisresearch reveals that the revolution in ht perspective is applied through 3 (three) stages of da'wah, namely (1) wiring; (2) Interaction with Society, which includes